PENGARUH MOTIVASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PERUMDA PASAR SEWAKADARMA KOTA DENPASAR - Ni Luh Ketut Ayu Sudha Sucandrawati; I Dewa Nyoman Usadha; Ni Ketut Mei Anjani (Universitas Mahendradatta, 2025)
Performance is the result of quality and quantity of work achieved by an employee incarrying out his duties according to the responsibilities given to him. Employee performancehas an important role in human resource management. Good performance can be influenced byseveral things, such as motivation and commitment from its employees. So that motivation andcommitment play an important role in achieving the Company's performance. The purpose ofthis study is to test: 1) The effect of motivation on employee performance at Perumda PasarSewakadarma Denpasar City. 2) The effect of organizational commitment on employee performance at Perumda Pasar Sewakadarma Denpasar City. 3) The influence oforganizational motivation and commitment on employee performance at Perumda PasarSewakadarma Denpasar City. The research design used in this study is quantitative. The dataanalysis technique used is multiple linear regression analysis using the SPSS application.Based on the results of the study, it was concluded that motivation partially had a positive andsignificant effect on employee performance at Perumda Pasar Sewakadarma. Organizationalcommitment partially has a positive and significant effect on employee performance atPerumda Pasar Sewakadarma. Organizational motivation and commitment simultaneouslyhave a positive and significant effect on employee performance at Perumda PasarSewakadarma Denpasar City.